The Influence of Content Marketing Strategy on Consumer Engagement on Social Media Platforms - Sugito, Sugito; Anto Tulim; Erbin Sitorus; Taufiq Azmi Harahap; Rayu Sri Wahyuni (Sean Institute, 2025)
Study This aim is to analyze influence strategy marketing content towards engagement consumers on the TikTok platform in context fashion industry. TikTok as a short video- based media own strong visual characteristics and level high interaction, so​ strategy content become factor determinant in interesting attention as well as build involvement users. Research This use approach quantitative with method survey through distributed Likert 1–5 questionnaire to users TikTok active 18–40 years old​ follow and consume fashion content. The sampling technique used is combined purposive sampling with stratified sampling based on gender and group age. Data analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS) to test influence variables quality content, consistency uploads, relevance content, and visual elements on consumer engagement. Research results show that all over dimensions strategy marketing content has influence positive and significant on engagement. Visual elements and quality content proven become the most dominant factor, followed by relevance content and consistency uploads. In addition, engagement was found play a role as an important mediator that connects strategy marketing content with purchase intention. Findings This support the theory of Media Richness, Source Credibility, Uses and Gratifications, and the Hierarchy of Effects Model in context short video- based digital marketing. In practical, research This give recommendation for fashion brands to prioritize visual quality, storytelling, and design encouraging content​ interaction organic use increase engagement and potential purchase. Research this also provides opportunity to study advanced with enter variables moderation and behavioral data current TikTok.